Novel spherical adsorbent based on waste coconut shells as well as preparation method and application of novel spherical adsorbent
Through the method of citric acid modification and chitosan coated coconut biochar, an efficient chitosan coated citric acid modified coconut biochar adsorbent was prepared, which solved the problems of unstable adsorbent in solution and low adsorption efficiency in the prior art, and achieved efficient adsorption of silver ions.
Patent Information
- Application Number
- CN202510510312.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-23
- Publication Date
- 2025-07-08
AI Technical Summary
It is difficult to prepare an adsorbent that can be stored stably in solution, has high adsorption efficiency and good adsorption ability to silver ions.
The method of modifying citric acid and coating coconut biochar with chitosan was prepared to improve the number of oxygen-containing functional groups and specific surface area of the biomass surface to enhance the adsorption capacity.
The rapid adsorption of silver ions by adsorbent in solution is achieved, with an adsorption rate of 80%, and the maximum adsorption amount is 195mg/g, which significantly improves the adsorption efficiency and ability.
Smart Images

Figure CN120268377A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of chemical adsorption, and relates to a coconut shell biochar spherical adsorbent modified with citric acid and coated with chitosan, and a preparation method and application thereof. Background Art
[0002] Silver has been widely used in industrial manufacturing due to its excellent ductility, thermal conductivity, photosensitivity, electrical and chemical properties, and antibacterial properties. It is widely used in the manufacture of high-precision physical instrument components, automation equipment, rockets, submarines, computers, nuclear facilities, and contact points in communication systems. However, in the production process of these devices, industrial wastewater containing low concentrations of silver ions will be generated. If these wastewaters are discharged directly without treatment, they will cause serious damage to terrestrial and aquatic ecosystems and may have a negative impact on human health through pathways such as the food chain. Therefore, adsorbing and recovering silver ions from wastewater not only has important environmental significance, but also can bring significant economic benefits.
[0003] As an agricultural waste, the rational use of coconut shells can help reduce waste and promote environmental protection. As a biomass material, the use of coconut shells is in line with the concept of sustainable development. Coconut shell-derived biochar has a developed pore structure and a high specific surface area, which makes it perform well in adsorption applications, especially in the fields of water treatment and air purification. At the same time, due to its high adsorption capacity and fast adsorption rate, it is widely used in gold extraction, removal of heavy metals in water, etc. In addition, coconut shell biomass, as a low-cost biomass-derived material, has the advantage of low price, which makes it more competitive in industrial applications.
[0004] Therefore, how to prepare an adsorbent that can be stably stored in a solution and has high silver ion adsorption efficiency and good adsorption capacity has become a technical problem that needs to be solved urgently in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a chitosan-coated citric acid-modified coconut shell biochar adsorbent and its preparation method and application. The adsorbent obtained by the preparation method of the chitosan-coated citric acid-modified coconut shell biochar adsorbent provided by the present invention can be stably stored in a solution, and has high silver ion adsorption efficiency and good adsorption capacity.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a method for preparing a citric acid modified-chitosan coated coconut shell biochar adsorbent, comprising the following steps:
[0008] (1) The coconut shell waste raw material is washed with deionized water to remove surface impurities, dried in an oven, crushed with a pulverizer, and then sieved with a sieve to prepare a coconut shell biomass material.
[0009] (2) Calcinate the biomass material obtained in step (1) in a muffle furnace, and grind it to obtain coconut shell-derived biochar.
[0010] (3) Add the coconut shell-derived biochar obtained in step (2) to a citric acid solution and mix well to obtain an acid-modified biomass material.
[0011] (4) Add chitosan to an acetic acid solution and mix well to form a hydrogel, and then add the biomass material obtained in step (3) thereto and mix well.
[0012] (5) Drop the mixed hydrogel obtained in step (4) into a NaOH solution to form microspheres.
[0013] (6) Immerse the microspheres obtained in step (5) in a mixed solution of methanol and pentanediol after hardening, wash, and dry to obtain a chitosan-coated citric acid-modified coconut shell biochar spherical adsorbent.
[0014] Preferably, the coconut shell powder in step (1) is sieved using a 100-mesh sieve.
[0015] Preferably, the calcination temperature in step (2) is 500 °C, the heating rate is 5 °C / min, and the holding time is 2 - 3 h.
[0016] Preferably, the concentration of citric acid in step (3) is 0.4 mol / L.
[0017] Preferably, the mass ratio of coconut shell biochar to chitosan in the chitosan solution in step (4) is (0.8 - 1):(2 - 2.5).
[0018] Preferably, the mass ratio of chitosan to acetic acid in step (4) is (2 - 2.5):(0.9 - 1.1).
[0019] Preferably, the concentration of the NaOH solution in step (5) is 0.5 - 0.8 mol / L.
[0020] Preferably, the volume ratio of methanol to glutaraldehyde in step (6) is 10:1.
[0021] The present invention provides an application of the chitosan-coated citric acid-modified coconut shell biochar adsorbent described in the above technical solution in adsorbing precious metal silver.
[0022] The present invention provides a method for preparing a spherical adsorbent material by modifying coconut shell biomass with citric acid and coating it with chitosan and its application, belonging to the field of adsorption. The preparation method provided by the present invention includes the following steps: (1) washing the surface impurities of the coconut shell waste raw material with deionized water, drying it in an oven, crushing it with a pulverizer, and then sieving it to make a coconut shell biomass material; (2) placing the biomass material obtained in step (1) in a muffle furnace for calcination and grinding to obtain coconut shell-derived biochar; (3) adding the coconut shell-derived biochar obtained in step (2) to a citric acid solution and mixing well to obtain an acid-modified biomass material; (4) adding chitosan to an acetic acid solution and mixing well to form a hydrogel, and then adding the biomass material obtained in step (3) thereto and mixing well; (5) dropping the mixed hydrogel obtained in step (4) into a NaOH solution to form microspheres; (6) immersing and washing the microspheres obtained in step (5) with a mixed solution of methanol and pentanediol after hardening, and drying to obtain a citric acid-modified chitosan-coated coconut shell spherical adsorbent. The present invention uses coconut shell as a raw material. By preparing coconut shell into biochar, the high carbon content and porous characteristics of biochar, as well as the large amount of oxygen-containing functional groups in coconut shell biochar, are utilized to improve the adsorption rate of silver ions; after modification with citric acid, the types and amounts of oxygen-containing functional groups (such as carboxyl groups, hydroxyl groups, etc.) on the surface of the biomass can be significantly increased. These functional groups can provide more adsorption sites, thereby improving the adsorption capacity of the biomass for pollutants, and by assisting in pore formation, the specific surface area and porosity of the biomass are increased, further enhancing its adsorption efficiency. Chitosan is a natural basic cationic polysaccharide, and its molecular chain contains rich active functional groups such as amino (-NH2) and hydroxyl (-OH). These functional groups can have electrostatic interaction, chelation or hydrogen bond interaction with pollutants (such as heavy metal ions, organic dyes, carbon dioxide, etc.), thereby significantly enhancing the adsorption capacity, and it is easy to form adsorption materials in various forms such as gels, microspheres, membranes, activated carbon, etc. The adsorbent obtained by modifying with citric acid and coating with chitosan greatly increases the groups in the adsorbent that can bind to metal silver ions and the specific surface area of the adsorbent, improves the adsorption efficiency and adsorption capacity of the adsorbent for metal silver ions, and enables the adsorbent to stably exist in the solution. The experimental results show that the chitosan-coated citric acid-modified coconut shell biochar adsorbent obtained by the preparation method provided by the present invention has an adsorption rate of 80% for silver ions in wastewater within 2 hours; it has a rapid adsorption efficiency for silver ions, with a maximum adsorption rate of 84% and a maximum monolayer adsorption amount of 195 mg / g, and has the characteristics of high adsorption efficiency and good adsorption capacity. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a process flow chart for preparing a citric acid-modified chitosan-coated coconut shell biochar adsorbent in an embodiment of the present invention;
[0024] Figure 2 SEM image of the citric acid-modified chitosan-coated coconut shell biochar adsorbent prepared in Example 1 of the present invention at 200 μm;
[0025] Figure 3 SEM images of the citric acid-modified chitosan-coated coconut shell biochar adsorbent prepared in Example 1 of the present invention at 20 μm and 5 μm; Detailed implementation manners
[0026] The present invention provides a preparation method of a chitosan-coated citric acid-modified coconut shell biochar adsorbent, comprising the following steps:
[0027] (1) Wash the surface impurities of the coconut shell waste raw material with deionized water, dry it in an oven, crush it with a crusher, and then sieve it to make a coconut shell biomass material;
[0028] (2) Place the biomass material obtained in step (1) in a muffle furnace for calcination and grinding to obtain coconut shell-derived biochar;
[0029] (3) Add the coconut shell-derived biochar obtained in step (2) to a citric acid solution and mix well to obtain an acid-modified biomass material;
[0030] (4) Add chitosan to an acetic acid solution and mix well to form a hydrogel, and then add the biomass material obtained in step (3) thereto and mix well;
[0031] (5) Drop the mixed hydrogel obtained in step (4) into a NaOH solution to form microspheres;
[0032] (6) Immerse the microspheres obtained in step (5) in a mixed solution of methanol and pentanediol for hardening, then wash and dry them to obtain a citric acid-modified chitosan-coated coconut shell spherical adsorbent.
[0033] The present invention preferably uses a citric acid solution to modify coconut shell biomass powder.
[0034] In the present invention, the preparation process of the coconut shell powder is preferably: wash, dry, crush and sieve the coconut shell in sequence to obtain coconut shell powder.
[0035] In the present invention, the coconut shell biomass powder is sieved with a 100-mesh sieve, which can ensure that the diameter of the biomass particles is less than 0.15 mm. It is not advisable to use a sieve with a mesh number greater than 100, which may cause the particles to be easily broken and agglomerated, affecting the adsorption performance. By limiting the particle size of the coconut shell powder within the above range, the present invention can increase the surface area of the biochar, thereby improving the adsorption performance and adsorption efficiency of the adsorbent.
[0036] The present invention places no special restrictions on the equipment and operations for crushing, and the equipment and operations well-known to those skilled in the art can be adopted.
[0037] In the present invention, the concentration of the citric acid solution is used in the range of 0.3 mol / L to 0.5 mol / L, and the more preferred concentration of the citric acid solution is 0.4 mol / L.
[0038] In the present invention, the mixed solution is dried to obtain the acid-modified biomass material.
[0039] In the present invention, the solvent used for washing is preferably deionized water; the number of washing times is preferably three. The present invention places no special restrictions on the equipment and operations for washing, and the common washing equipment and operations used by those skilled in the art can be adopted. The present invention can wash away the impurities on the surface of the coconut shell through washing.
[0040] In the present invention, the drying temperature is preferably 80 °C, and the drying time is preferably 2 days. The present invention places no special restrictions on the drying equipment, and the common drying equipment used by those skilled in the art can be adopted. The present invention can fully remove the moisture in the coconut shell through drying, which is beneficial for subsequent preparation.
[0041] In the present invention, the calcination of the coconut shell biochar is preferably carried out in a muffle furnace; the calcination temperature is preferably 400 °C to 600 °C, more preferably 500 °C; the calcination time is preferably 1.5 to 2.5 h, more preferably 2 h. After the calcined product is cooled to room temperature, it can be used for the next step of grinding. The present invention limits the calcination temperature and time within the above range to ensure the shaping and stability of the coconut shell biochar, and to make the biochar have a higher porosity, thereby improving the adsorption effect of the biochar.
[0042] After the calcination is completed, the present invention preferably cools, grinds and sieves the calcined product in sequence to obtain the chitosan-coated citric acid-modified coconut shell biomass.
[0043] The present invention places no special restrictions on the operation of cooling, and it is only necessary to cool the calcined product to room temperature.
[0044] The present invention places no special restrictions on the equipment and operations for grinding, and the operations well-known to those skilled in the art can be adopted.
[0045] The present invention preferably uses water, acetic acid and chitosan to prepare a hydrogel to obtain a mixed solution a. (1) In the present invention, the proportion of acetic acid in water is 1.8% - 2.2%, more preferably 2%;
[0046] (2) In the present invention, the addition amount of chitosan in 50 ml of acetic acid solution is 2 - 2.5 g, more preferably 2.5 g, which can have better shaping and adsorption effects;
[0047] (3) In the present invention, the stirring time of the mixed solution of water, acetic acid, and chitosan at a rotation speed of 180 r / min should not exceed 12 h, and more preferably 6 h.
[0048] The present invention preferably slowly adds coconut shell biomass during the stirring of the mixed solution a to obtain a mixed solution b.
[0049] In the present invention, adding 1 g of coconut shell biomass to the mixed solution a in five portions of 0.2 g each can achieve better coating of the coconut shell powder.
[0050] In the present invention, the stirring time of the mixed solution b should be controlled within 12 hours, and more preferably 8 hours.
[0051] In the present invention, the preparation process of the coconut shell powder is preferably as follows: the coconut shell is successively washed, dried, crushed, and sieved to obtain coconut shell powder.
[0052] In the present invention, the coconut shell biomass powder is sieved through a 100-mesh sieve, which can ensure that the diameter of the biomass particles is less than 0.15 mm. By limiting the particle size of the coconut shell powder within the above range, the present invention can increase the surface area of the biochar, thereby improving the adsorption performance and adsorption efficiency of the adsorbent.
[0053] The present invention has no special limitation on the equipment and operation of the crushing, and the equipment and operation well-known to those skilled in the art can be used.
[0054] In the present invention, the mass ratio of coconut shell biochar to chitosan is (0.8 - 1):(2 - 2.5), and the more preferred mass ratio is 1:2.5. With the above mass ratio, the coconut shell and chitosan can be better and fully mixed, which is more conducive to the subsequent coating of chitosan on the coconut shell biochar.
[0055] The present invention uses a titration method to fix the mixed solution b with a NaOH solution to form microspheres.
[0056] In the present invention, the coagulation solution is preferably a NaOH solution; the concentration of the NaOH solution is preferably 0.8 - 1.0 mol / L, and more preferably 1 mol / L. By limiting the type and concentration of the coagulation solution within the above range, the present invention can make the mixed solution form microspheres, and no microspheres can be obtained if the concentration of the NaOH solution is too low or too high.
[0057] In the present invention, the dropping rate into the coagulation solution is 0.03 - 0.06 ml / 3 - 4 s; more preferably 0.04 ml / 3 - 4 s. By controlling the dropping rate within the above range, the present invention is conducive to the formation of microspheres.
[0058] In the present invention, chitosan-coated citric acid-modified coconut shell biomass is dropped into a coagulation solution to form microspheres. The principle is that chitosan molecules contain a large number of amino groups (-NH2) and hydroxyl groups (-OH). These groups can be protonated under acidic conditions and dissolve in water. When the chitosan solution contacts the sodium hydroxide solution, the hydroxide ions (OH-) in sodium hydroxide will neutralize the protonated amino groups in the chitosan molecules, restoring them to the unprotonated state. At this time, the amino and hydroxyl groups on the chitosan molecular chain can re-form intermolecular hydrogen bonds, thereby enhancing the intermolecular interaction. And under alkaline conditions, the amino groups of chitosan molecules are deprotonated and carry positive charges. These positively charged groups will form a network structure through electrostatic interaction. This electrostatic interaction is one of the important driving forces for chitosan gelation. With the enhancement of intermolecular hydrogen bonds and electrostatic interactions, the chitosan molecular chains gradually aggregate and form a three-dimensional network structure. This network structure can capture and fix water, thus turning the solution into a gel state. Finally, when the chitosan-coated biomass is dropped into the sodium hydroxide solution, the presence of the biomass may further enhance the stability of the gel. Components such as cellulose and lignin in the biomass can bind to the chitosan molecular chain through hydrogen bonds or hydrophobic interactions, thereby further stabilizing the gel network.
[0059] In the present invention, after the titration is completed, it needs to be left standing. Preferably, the standing time is preferably 24 hours, and the standing temperature is room temperature. By standing, the microspheres can be better formed and solidified.
[0060] In the present invention, the solvent for washing is preferably deionized water; the number of washing times is preferably three times, and the washing is carried out until the pH of the washing solution is neutral.
[0061] After obtaining the microspheres in the present invention, the microspheres are placed in a mixed solution of methanol and pentanediol to form a cross-linking reaction, thereby obtaining a chitosan-coated citric acid-modified coconut shell biomass adsorbent.
[0062] In the present invention, the solvent in the glutaraldehyde solution is preferably methanol; the volume content of glutaraldehyde in the glutaraldehyde solution is preferably 9-10%, and further preferably 9.1%. Limiting the volume content of glutaraldehyde within the above range in the present invention can facilitate the cross-linking reaction between chitosan in the microspheres and glutaraldehyde, enabling the microspheres to have the ability to stably exist in both acidic and alkaline solutions.
[0063] The invention proposes an optimized treatment step: standing after the microspheres are mixed with the glutaraldehyde solution. This standing process helps the cross-linking reaction to proceed fully. Specifically, 24 hours is the optimal choice for the cross-linking reaction time; the reaction temperature is preferably room temperature. Through this cross-linking reaction, the surface of the microspheres can be more effectively combined with chitosan, and at the same time, the stability of the microspheres in an acidic environment can be significantly improved.
[0064] After the cross-linking reaction was completed, the present invention further optimized the post-treatment steps of the product. First, the cross-linked product was separated by a sieve spoon; subsequently, the separated solid was placed in a petri dish and air-dried naturally, and finally the chitosan-coated citric acid-modified coconut shell biochar adsorbent was obtained.
[0065] The present invention uses coconut shell as a raw material, converts it into biochar, and utilizes its high carbon content, porous structure characteristics, and the abundant oxygen-containing functional groups on the surface of coconut shell biochar to improve the adsorption efficiency of silver ions. Chitosan forms chelate complexes with silver ions in water by virtue of functional groups such as amino and hydroxyl groups on its macromolecular linear backbone. By coating coconut shell biochar with chitosan, the number of active groups and the specific surface area of the adsorbent are greatly increased, thereby significantly enhancing its adsorption efficiency and adsorption capacity for metal silver ions and ensuring the stability of the adsorbent in solution.
[0066] The present invention significantly increases the number of active groups on the surface of the adsorbent, which can effectively bind to metal silver ions, and at the same time greatly increases the specific surface area of the adsorbent. Therefore, the adsorption efficiency and adsorption capacity of the adsorbent for metal silver ions have been significantly improved.
[0067] The following content will elaborate on the technical solution of the present invention in detail and completely through specific embodiments of the present invention. It should be noted that the listed embodiments are only several examples of the present invention and do not cover all implementation manners of the present invention. Based on these embodiments, other implementation manners deduced by those skilled in the art without creative work should be included in the protection scope of the present invention.
[0068] Example 1
[0069] A preparation method of a chitosan-coated citric acid-modified coconut shell biomass biochar adsorbent includes the following steps:
[0070] (1) Wash the surface impurities of the coconut shell waste raw material with deionized water, dry it in an oven at 80 °C for 48 h, crush it with a crusher, and then screen it with a 100-mesh sieve to make coconut shell biomass material;
[0071] (2) Place the biomass material obtained in step (1) in a muffle furnace and calcine it at 500 °C for 2 h, grind it, and the particle size after grinding is less than 0.15 mm to obtain coconut shell-derived biochar;
[0072] (3) Add the coconut shell-derived biochar obtained in step (2) to a 0.4 mol / L citric acid solution and mix well to obtain acid-modified biomass material, dry it in an oven at 80 °C for 48 h, and then grind it, with a particle size less than 0.15 mm;
[0073] (4) Add 2.5 g of chitosan to 50 ml of 2% acetic acid solution and mix well to form a hydrogel. Then add the biomass material obtained in step (3) above, mix well, and stir at 180 r / min for 6 h;
[0074] (5) Drop the mixed hydrogel obtained in step (4) into 1 mol / L NaOH solution to form microspheres, and let it stand for 24 hours. After standing, sieve with a sieve spoon, and wash the sieved microspheres with deionized water until the pH of the washing liquid is neutral;
[0075] (6) Let the microspheres obtained in step (5) stand for 24 h to harden, then fully immerse them in a mixed solution of methanol and glutaric acid, wash, and dry to obtain a citric acid-modified chitosan-coated coconut shell spherical adsorbent. The volume content of glutaraldehyde in the glutaraldehyde solution is 9.1%
[0076] The scanning electron micrograph of the chitosan-coated citric acid-modified coconut shell biochar adsorbent prepared in Example 1 at 200 μm is as Figure 2 shown. As can be seen from Figure 2 it, the prepared chitosan-coated citric acid-modified coconut shell biochar adsorbent is in the form of microspheres.
[0077] The scanning electron micrographs (20 μm and 5 μm) of the chitosan-coated citric acid-modified coconut shell biochar adsorbent prepared in Example 1 are as Figure 3 shown. It can be observed from the figure that the surface of the adsorbent shows an obvious porous structure, and the surface of the microspheres is composed of spherical particles arranged closely. They closely surround the porous structure formed by the biochar, and its excellent crystal form and pore structure can be clearly seen from the image.
[0078] Comparative Example 1
[0079] A preparation method of a chitosan-coated citric acid-modified coconut shell biochar adsorbent, comprising the following steps:
[0080] (1) Wash the surface impurities of the coconut shell waste raw material with deionized water, dry it in an oven at 80 °C for 24 h, crush it with a crusher, and then sieve it with a 100-mesh sieve to make a coconut shell biomass material;
[0081] (2) Place the biomass material obtained in step (1) in a muffle furnace and calcine it at 500 °C for 2 h, then grind it. The particle size after grinding is less than 0.15 mm to obtain coconut shell-derived biochar;
[0082] (3) Add the coconut shell-derived biochar obtained in step (2) to 0.4 mol / L citric acid solution and mix well to obtain an acid-modified biomass material. Dry it in an oven at 80 °C for 24 h, and then grind it. The particle size is less than 0.15 mm;
[0083] (4) Add 2.5 g of chitosan to 50 ml of 2% acetic acid solution and mix well to form a hydrogel. Then add the biomass material obtained in step (3) above, mix well, stir at 180 r / min for 6 h, directly dry after stirring, and grind into an adsorbent powder with a particle size less than 0.15 mm.
[0084] Application Example 1 and Comparative Example 1
[0085] Take 30 mg each of the chitosan-coated citric acid-modified coconut shell biochar adsorbents prepared in Example 1 and Comparative Example 1, and add them to 100 mL of a solution with a silver ion concentration of 50 mg / L. Subsequently, place the above solution in a water bath constant temperature oscillator and perform continuous adsorption treatment at 25 °C and 180 r / min for 24 hours. After adsorption is completed, take the supernatant and measure the residual concentration of silver ions in the filtrate by an atomic absorption spectrometer.
[0086] In addition, the total pore volume, average pore diameter, and specific surface area of the chitosan-coated citric acid-modified coconut shell biochar adsorbents prepared in Example 1 and Comparative Example 1 were measured by a BET specific surface area tester.
[0087] Table 1 Total pore volume, average pore diameter, and specific surface area of the chitosan-coated citric acid-modified coconut shell biochar adsorbents prepared in Example 1 and Comparative Example 1
[0088] Example <![CDATA[Total pore volume (cm 3 / g)]]> Average pore diameter (μm) <![CDATA[Specific surface area (m 2 / g)]]> Example 1 0.126895 0.0049568 114.59 Comparative Example 1 0.065896 0.0012658 69.65
[0089] As can be seen from Table 1, the specific surface area of the chitosan-coated citric acid-modified coconut shell biochar adsorbent prepared in Comparative Example 1 is significantly lower than that in Example 1. The reason is that in Example 1, a microsphere adsorbent was used, while in the comparative example, a powder was used. Microsphere adsorbents usually have a higher specific surface area and a more developed pore structure, which enables them to provide more active sites for adsorption. In addition, the porous structure of the microspheres is conducive to the diffusion and adsorption of adsorbates, thereby improving the adsorption efficiency. And the spherical structure of the microspheres helps to reduce the mass transfer resistance, enabling the adsorbate to reach the adsorption sites more quickly. This structural advantage makes the microsphere adsorbent exhibit faster kinetic characteristics during the adsorption process. The adsorption efficiency of the microsphere adsorbent obtained in Example 1 for 50 mg / L Ag ions can reach up to 84%, while the adsorption efficiency of the powder adsorbent obtained in the comparative example for 50 mg / L Ag ions is only 61% at most. For the powder adsorbent in Comparative Example 1, the pore diameter and pore volume did not reach the optimal values. Therefore, the microsphere adsorbent in Example 1 and its ratio, firing temperature, time and other conditions are the optimal conditions for preparing the chitosan-coated citric acid-modified coconut shell biochar adsorbent.
[0090] After testing the adsorption performance of the adsorbent prepared in Example 1, the results showed that the concentration of silver ion solution before adsorption was 50 mg / L, and the concentration decreased to 8 mg / L after adsorption. Within 2 hours, the adsorption rate of silver ions in wastewater by this adsorbent reached 80%. Compared with other biochar-modified adsorption materials that usually require more than 8 hours to achieve good adsorption effects, the chitosan-coated citric acid-modified coconut shell biochar microsphere adsorbent demonstrated a faster adsorption efficiency. In addition, compared with powder adsorbents, the microsphere adsorbent not only has a more convenient and environmentally friendly recovery method but also can effectively avoid the problem of secondary pollution caused by incomplete recovery.
[0091] Finally, the equilibrium adsorption rate of the chitosan-coated citric acid-modified coconut shell biochar adsorbent prepared in Example 1 can reach 84%, and the maximum monolayer adsorption capacity is 195 mg / g, showing excellent adsorption performance for precious metal silver.
[0092] It should be noted that the above content is only the preferred embodiment of the present invention. Those of ordinary skill in the art can further improve and optimize the present invention without departing from the principle of the present invention, and these improvements and optimizations also fall within the protection scope of the present invention.
Claims
1. A preparation method of a citric acid-modified chitosan-coated coconut shell biochar spherical adsorbent, comprising the following steps: (1) Wash the surface impurities of the coconut shell waste raw material with deionized water, dry it in an oven, crush it with a crusher, and then screen it with a sieve to make a coconut shell biomass material. (2) Place the biomass material obtained in step (1) in a muffle furnace for calcination and grinding to obtain coconut shell-derived biochar. (3) Add the coconut shell-derived biochar obtained in step (2) to a citric acid solution and mix well to obtain an acid-modified biomass material. (4) Add chitosan to an acetic acid solution and mix well to form a hydrogel, and then add the biomass material obtained in step (3) thereto and mix well. (5) Drop the mixed hydrogel obtained in step (4) into a NaOH solution to form microspheres. (6) Immerse the microspheres obtained in step (5) in a mixed solution of methanol and glutaric alcohol for hardening, wash them, and dry them to obtain a citric acid-modified chitosan-coated coconut shell-derived biochar spherical adsorbent.
2. The preparation method according to claim 1, wherein: In step (1), the coconut shell powder should be screened with a 100-mesh sieve.
3. The preparation method according to claim 1, wherein: In step (2), the calcination temperature is 500 °C, the heating rate is 5 °C / min, and the heat preservation time is 2-3 h.
4. The preparation method according to claim 1, characterized in that: In step (3), the concentration of citric acid is 0.4 mol / L.
5. The preparation method according to claim 1, characterized in that: In step (4), the mass ratio of coconut shell biochar to chitosan in the chitosan solution is (0.8-1):(2-2.5).
6. The preparation method according to claim 1, wherein: In step (4), the mass ratio of chitosan to acetic acid is (2-2.5):(0.9-1.1).
7. The preparation method according to claim 1, characterized in that: In step (5), the concentration of the NaOH solution is 0.5-0.8 mol / L.
8. The preparation method according to claim 1, wherein: In step (6), the volume ratio of methanol to glutaraldehyde is 10:
1.
9. According to the preparation method described in claim 1, the prepared spherical adsorbent adsorbs silver ions in the wastewater discharged from electroplating, photography, electronic manufacturing, medicine, etc.
Citation Information
Cited By
High-selectivity activated carbon for water purification and preparation method thereof
CN121372369A
A highly selective activated carbon for water purification and its preparation method
CN121372369B